Mimosine Dipeptide Enantiomsers: Improved Inhibitors against Melanogenesis and Cyclooxygenase - Binh Cao Quan Nguyen; Shinkichi Tawata (Molecules, 2015)
Melanogenesis plays an important role in the protection of skin against UV through production of melanin pigments, but abnormal accumulation of this pigment causes unaesthetic hyperpigmentation. Much effort is being made to develop effective depigmenting agents. Here, we show for the first time that a small library of mimosine dipeptide enantiomers (Mi-L/D-amino acid) inhibit the melanogenesis in B16F10 melanoma cells by down-regulating the cellular tyrosinase with little effect on their growth or viability. Two of them, Mi-D-Trp and Mi-D-Val, turned out to be the most potent inhibitors on melanin content and cellular tyrosinase in B16F10 melanoma cells. In addition, most of the mimosine dipeptides were more potent than mimosine for inhibiting cyclooxygenase 1 (COX-1) with IC50 of 18–26 μM. Among them, Mi-L-Val and Mi-L-Trp inhibited cyclooxygenase 2 (COX-2) more potently than indomethacin, with IC50 values of 22 and 19 μM, respectively. Taken together, our results suggest the possibility that mimosine dipeptides could be better candidates (than mimosine) for anti-melanogenic (skin hyperpigmentation treatment) and cyclooxygenase (COX) inhibition.